A survey of nocturnal hypoxaemia and health related quality of life in patients with cryptogenic fibrosing alveolitis. Issue 6 (1st June 2001) - Clark, M; Cooper, B; Singh, S; Cooper, M; Carr, A; Hubbard, R
Abstract : BACKGROUND: A survey of overnight oximetry was conducted to estimate the prevalence of nocturnal hypoxaemia in patients with cryptogenic fibrosing alveolitis and to establish whether nocturnal hypoxaemia is related to quality of life. METHODS: All patients with cryptogenic fibrosing alveolitis attending Nottingham City Hospital were invited to enter the study. Spirometric measurements and capillary blood gas tensions were obtained and overnight oxygen saturation was recorded at home. Quality of life was assessed using the Short Form-36, Chronic Respiratory Questionnaire, Hospital Anxiety Depression Scale, and Epworth Sleepiness Score questionnaires. RESULTS: Sixty seven eligible patients were identified and 50 agreed to enter the study, although two were subsequently excluded because they already used oxygen overnight. In the remaining 48 the mean (SD) overnight oxygen saturation (Sao 2 ) was 92.5 (4.3)% and the median number of dips greater than 4% per hour was 2.3 (interquartile range 1.5–5.3). Daytime oxygen level predicted mean overnight Sao 2 (1.94%/kPa, 95% CI 1.22 to 2.66, p<0.001) but percentage predicted forced vital capacity (FVC) did not (0.018%/% predicted FVC, 95% CI –0.04 to 0.08, p=0.5). Nocturnal hypoxaemia was associated with decreased energy levels and impaired daytime social and physical functioning, and these effects were independent of FVC. CONCLUSIONS: Nocturnal hypoxaemia is common in patients with cryptogenic fibrosing alveolitis and may have an impact on health related quality of life.